Massive invasion on a Triatominae insectarium (Hemiptera: Heteroptera: Reduviidae) by Attagenus fasciatus (Thunberg, 1795) (Coleoptera: Dermestidae: Attageninae) - de Oliveira, Jader; Háva, Jiří; Rosa, João Aristeu da [UNESP]; Gil-Santana, Hélcio Reinaldo (FapUNIFESP (SciELO), 2023)
Background: Triatominae are vectors of the protozoan Trypanosoma cruzi, the causative agent of Chagas disease. This study aims to report an infestation on Triatominae colonies by a beetle, previously identified as a pest. Methods: The management of these colonies should be improved to maximize their usefulness, and factors that may cause harm to them should be avoided as much as possible. Results: This is the first report on a coleopteran infestation on living Triatominae colonies worldwide. Conclusions: The present record provides an important warning to researchers who maintain insectaries in general, especially those who rear triatomines, to carry protective measures against such invasions.
Keywords: Biological collections; Conservation; Living collection; Pests; Triatominae insectarium